2019
DOI: 10.5271/sjweh.3843
|View full text |Cite
|
Sign up to set email alerts
|

Educational differences in duration of working life and loss of paid employment: working life expectancy in The Netherlands

Abstract: This paper adds the life course perspective in a broad age range of the Dutch population using state of the art methodology. The paper offers insight into the educational inequalities in working life expectancy and working years lost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 22 publications
8
48
1
1
Order By: Relevance
“…A recent Dutch study found that compared with highly educated workers, the WLE at age 30 years of low-educated men and women was reduced by 7.3 years and 9.9 years, respectively. 25 Low-educated persons often lack vocational education. As compared with highly educated persons, they usually enter the workforce earlier and more frequently are occupied in jobs with physically demanding tasks.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Dutch study found that compared with highly educated workers, the WLE at age 30 years of low-educated men and women was reduced by 7.3 years and 9.9 years, respectively. 25 Low-educated persons often lack vocational education. As compared with highly educated persons, they usually enter the workforce earlier and more frequently are occupied in jobs with physically demanding tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Third, while we previously looked at the situation at age 50, we now focus on partial life expectancies between age 50-59 and 60-69, respectively. Focusing on these two age intervals provides a Table 1 Descriptive statistics for men (weighted with sample weights) from SHARE wave 7 in 2017 (sample size, share of men without activity limitations, good physical health, and good cognition ages 50 years and older) and life expectancy at age 60 in 2017, LFP rates for age group 60-64 in 2017, and the current general retirement age in 2019 * Represents the retirement age of the national pension, not the earnings-related pension Sources: SHARE, Eurostat; for retirement ages: https ://www.etk.fi/en/the-pensi on-syste m/inter natio nal-compa rison /retir ement -ages/ (Dudel et al 2018;Lorenti et al 2019;Lozano and Rentería 2019;Pedersen et al 2020;Robroek et al 2020), with several of them including information on certain health aspects like disability, depressive symptoms or self-perceived health (de Wind et al 2018;Lievre et al 2007;Pedersen et al 2019;van der Noordt et al 2019;Wubulihasimu et al 2015). The choice of health dimensions in our investigation is based on their relevance for individuals' performance in the labour market.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to cognition, studies have found that cognitive ability levels predict individual productivity better than any other observable individual characteristics and that they are increasingly relevant for labour market performance (Schmidt and Hunter 2004;Spitz-Oener 2006). Age-related cognitive decline is usually characterized by having difficulty recalling facts (Ritchie and Tuokko 2010), but may additionally affect processing speed (Salthouse 2010). Immediate word recall, our measure for cognitive health status, is a by now well-established indicator for cognitive functioning and abilities (Salthouse 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite many attempts to reduce socioeconomic health differences, such differences remain large and persistent ( 1 , 2 ). As, in the work domain, low-educated employees much more often prematurely leave the labor force due to health-related problems than their higher-educated counterparts ( 2 – 4 ), it is worrying that lower-educated employees are often difficult to reach in research and intervention efforts aimed at improving their situation ( 5 , 6 ). Through absenteeism, presenteeism, and high staff turnover, this has substantial financial implications for employers too ( 7 ).…”
Section: Introductionmentioning
confidence: 99%